On Behalf of all and for all! - Jarmus, Andrew (Winnipeg Ecclesia publishing Co. Ltd, 1989)
Contained in this book is the complete text of the Divine Liturgy of St. John Crysostom in Ukrainian and English. Both the Ukrainian and English texts contain directions explaining what is happening at various points in the service. Additionally, the Ukrainian text is illustrated, and the English text is annotated with comments designed to guide the worshiper into a deeper, fuller experience of the Divine Liturgy.
Keywords: Culture